Climate change effects on biodiversity, ecosystems, ecosystem services, and natural resource management in the United States - Weiskopf, Sarah R.; Rubenstein, Madeleine A.; Crozier, Lisa G.; Gaichas, Sarah; Griffis, Roger; Halofsky, Jessica E.; Hyde, Kimberly J.W.; Morelli, Toni Lyn; Morisette, Jeffrey T.; Muñoz, Roldan C.; Pershing, Andrew J.; Peterson, David L.; et al. (The Science of the total environment, 2020)
Climate change is a pervasive and growing global threat to biodiversity and ecosystems. Here, we present the most up-to-date assessment of climate change impacts on biodiversity, ecosystems, and ecosystem services in the U.S. and implications for natural resource management. We draw from the 4th National Climate Assessment to summarize observed and projected changes to ecosystems and biodiversity, explore linkages to important ecosystem services, and discuss associated challenges and opportunities for natural resource management. We find that species are responding to climate change through changes in morphology and behavior, phenology, and geographic range shifts, and these changes are mediated by plastic and evolutionary responses. Responses by species and populations, combined with direct effects of climate change on ecosystems (including more extreme events), are resulting in widespread changes in productivity, species interactions, vulnerability to biological invasions, and other emergent properties. Collectively, these impacts alter the benefits and services that natural ecosystems can provide to society. Although not all impacts are negative, even positive changes can require costly societal adjustments. Natural resource managers need proactive, flexible adaptation strategies that consider historical and future outlooks to minimize costs over the long term. Many organizations are beginning to explore these approaches, but implementation is not yet prevalent or systematic across the nation. •Climate change is affecting ecosystems at multiple scales.•Individual/species: changes in morphology and behavior, phenology, and range shifts observed•Ecosystems: shifts in productivity, species interactions, and emergent properties observed•Together, these changes are impacting ecosystem services and human well-being.•Natural resource managers need proactive, flexible approaches to deal with changes.